Presentation, Diagnosis and Treatment of Mixed Vaginitis - Perveen, Safia; Shah, Fatima; Zaman, Salma; Mahmood, Fizza; Suleman Azhar, Muhammad; Mahmood, Usama (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Mixed vaginitis is commonly observed in many women at their fertility age which brings negative impact on women well-being. Aim: To analyze the presentation, diagnosis and treatment scheme of mixed vaginitis. Study Design: Cross sectional analytical Place and duration of study: Department of Obstetrics & Gynaecology, DHQ/Teaching Hospital Sahiwal from 1st January 2021 to 30th June 2021. Methodology: Eighty females suffering from more than one type of vaginitis were enrolled as study participant after their complete diagnosis. High vaginal swabs, culturing requiring gram staining and lab testing through PCR was performed. Results: The mean age of 26.3±3.5 years. There were 11.25% cases with aerobic vaginitis, 43.75 % of bacterial vaginitis, 25% of vulvovaginal candidiasis, 11.25% allergic vaginitis and 8.75% of trichomoniasis in a mixed presentation. 75% of cases were treated with tropical anti bacterial or antifungal agents and 33% those cases treated with metronidazole in a combination with other drugs as well. Conclusion: Mixed vaginitis is treated on basis of its presentation with various diagnosis protocols.